SAT0596 Thoracic involvement at diagnosis drives a differentiated clinical presentation of sarcoidosis: analysis of 1245 patients (SARCOGEAS-SEMI). (12th June 2018) - Retamozo, S.; Brito-Zerón, P.; Pérez-Alvarez, R.; Kostov, B.; Feijoo Masso, C.; Fraile, G.; Gómez-de-la-Torre, R.; De-Escalante, B.; López-Dupla, M.; Alguacil, A.; Chara-Cervantes, J.; Pérez-Conesa, M.; et al.
Abstract : Objectives: To analyse whether thoracic involvement at diagnosis is associated with a specific clinical presentation of sarcoidosis. Methods: The SARCOGEAS-SEMI is a nationwide registry of patients with sarcoidosis. Radiographic stages at diagnosis were classified as stage 0 (normal), stage I (only bilateral hilar lymphadenopathy -BHL-), stage II (BHL +pulmonary infiltrates), stage III (only infiltrates) and stage IV (fibrosis). Results: The cohort consisted of 1245 patients (722 women, 523 men, mean age at diagnosis 47 years). Pulmonary imaging data at diagnosis was available in 1230 patients including 395 (32%) with stage I, 500 (40%) with stage II, 195 (16%) with stage III and 42 (3%) with stage IV. Patients with no thoracic involvement (stage 0) were more frequently women (73% vs 56%, p=0.002), older (52.1 vs 46.8 years, p=0.001) and had a higher frequency of skin (54% vs 34%, p<0.001) and neurological (14% vs 6%, p=0.004) involvements in comparison with those with stages I-IV. Patients without ILD (stage I) were more frequently women (61% vs 54%, p=0.031), had a higher frequency of fever (27% vs 19%, p=0.002), skin (43% vs 29%, p<0.001) and salivary gland involvement (8% vs 3%, p=0.001), and a lower frequency of respiratory symptoms (37% vs 54%, p<0.001) and liver involvement (9% vs 16%, p=0.001) with respect to those with ILD (stages II-IV). Conclusions: A specific clinical and epidemiological pattern of disease presentation was found in patients with no thoracic involvement and in those presenting with interstitial lung disease at diagnosis. Disclosure of Interest: None declared